Antigens of bovine leukosis virus and precipitating antibodies in sera of cattle - Cunha, Raymundo G.; Teixeira, Adenauer Cruz; Souza, Dilma Moura de (Pesquisa Agropecuaria Brasileira, 2014)
Two antigens for agar gel immunodiffusion (AGID) test in diagnosing Bovine Leukosis Virus (BLV) infection were compared by examination of 117 bovine sera: a dual antigen, containing both glycoprotein gp 51 and internal polypeptide p 24/25 and the Leukassay B antigen that contains only the glycoprotein. Similar results were shown by both antigens. Seven hundred and forty six bovine serum samples, collected in 65 farms of 20 counties of Rio de Janeiro State, were examined by AGID test, using routinely the dual antigen. Only 49 sera from Petropolis county were checked with Leukassay B antigen. Two hundred and one sera showed positive reactions (26.99%), indicative of BLV infection which appeared well disseminated among cattle from different regions of the State.